Obesity, sarcopenia, sarcopenic obesity and reduced mobility in Brazilian older people aged 80 years and over - Santos, Vanessa Ribeiro dos [UNESP]; Gomes, Igor Conterato; Bueno, Denise Rodrigues; Destro Christofaro, Diego Giulliano [UNESP]; Freitas, Ismael Forte [UNESP]; Gobbo, Luis Alberto [UNESP] (Inst Israelita Ensino & Pesquisa Albert Einstein, 2017)
Objective: To analyze which abnormalities in body composition (obesity, sarcopenia or sarcopenic obesity) are related to reduced mobility in older people aged 80 years and older. Methods: The sample included 116 subjects aged 80 years and older. The body composition was measured using dual-energy X-ray absorptiometry (DXA) and mobility was assessed by motor tests. The chi(2) test was used to analyze the proportion of older people with sarcopenia, obesity and sarcopenic obesity based on sex as well as to indicate an association between obesity, sarcopenia, sarcopenic obesity and mobility. Binary logistic regression, adjusted for the variables (sex and osteoarticular diseases), was used to express the magnitude of these associations. One-way analysis of variance was used to compare the mobility of four groups (Normal, Obesity, Sarcopenia and Sarcopenic Obesity). Results: The Sarcopenia Group had lower performance in the lower limbs strength test and in sum of two tests compared with Obesity and Normal Groups. Older people with sarcopenia had higher chance of reduced mobility (OR: 3.44; 95%CI: 1.12-10.52). Conclusion: Older people aged 80 years and older with sarcopenia have more chance for reduction in mobility.
Keywords: Aging; Body composition; Gait; Densitometry; Aged, 80 and over; Aged; Sarcopenia; Obesity; Mobility limitation